Kesehatan kerja dan penyakit akibat kerja kasus kondisi emergensi di tempat kerja - Kamesha, Ammara Daffa; Aziza, Almira Hana; Lubis, Aisyah Fahira; Zaharani, Yulanda Tantra (Public Health Risk Assesment Journal, 2024)
Workplace accidents refer to unintended incidents or events resulting in human loss, disruption of work processes, or property damage in industrial work environments. The impacts of workplace accidents include physical injuries, work-related illnesses, property damage, economic losses, and social consequences. Various steps can be taken to prevent workplace accidents, including the implementation of workplace safety regulations and standards, compliance with safety requirements, provision of safety education and training for workers, safety supervision and inspections, and the formation of a safety culture in the workplace. The Indonesian government has taken steps through various policies to reduce workplace accident incidents. The aluminum industry is one sector with a high risk of workplace accidents. This is due to the aluminum production process involving hazardous stages, heavy machinery use, specialized equipment, and complex chemical processes. One emergency situation that can occur in the aluminum industry is fire, as seen in the case of the fire at PT Aluminium Indonesia's factory in Pergudangan Manis, Curug, Tangerang. This fire was caused by sparks from welding that hit aluminum coils intended for making aluminum foil near the welding site. The author aims to delve deeper into this case, including the risk factors, hazards faced, and ways to prevent and handle such fire incidents. This objective aims to provide a better understanding of workplace accidents, especially fires, in the aluminum industry and how to prevent them.